Use of HRM-Analysis of the Melting Curves Obtained after Amplification of VNTR-Loci for Identification and Differentiation of Brucella Strains - E. A. Anisimova; D. A. Mirgazov; E. A. Dodonova; I. A. Elizarova; E. V. Pankova; K. A. Osyanin (Проблемы особо опасных инфекций, 2024)
The aim of the present study was to evaluate the effectiveness of analysis of the high resolution melting curves obtained after amplification of VNTR loci for the identification and differentiation of Brucella strains.Materials and methods. 16 strains of Brucella species – B. canis (n=1), B. abortus (n=9), B. melitensis (n=2), B. suis (n=4) – of different geographical origin were used as objects of the research. The MLVA-typing was performed using conventional PCR followed by separation of amplicons in agarose gel and real-time PCR with post-amplification analysis of the curves of VNTR loci melting in the presence of intercalating dye SybrGreen. Bioinformatics analysis was conducted with the help of Vector NTI 9.1, Mega 11 software (MUSCLE algorithm). Phylogenetic analysis was carried out applying UPGMA method using the Mega 11 program.Results and discussion. MLVA approach based on the analysis of the melting point curves of the obtained after amplification of VNTR-loci PCR fragments has shown that each of the 16 strains of Brucella is characterized by a unique melting temperature profile. PCR followed by electrophoresis has demonstrated that despite the high variability of the used VNTR sequences (h=0.48…0.74), only post-amplification melting curves of the Bru7, Bru9, Bru18, Bru21 loci had sufficient information content to determine the genetic polymorphism of the studied Brucella strains. Based on the results of phylogenetic analysis of the Bru7, Bru9, Bru18, Bru21 sequences, it has been found that the majority of the studied Brucella strains are distributed in the dendrogram in accordance with their taxonomic and geographical position. Thus, HRM analysis of melting curves obtained after amplification of the Bru7, Bru9, Bru18, Bru21 loci has the potential to be used for differentiating Brucella strains.